Optical properties and kinetic behaviour of some chemical and biological species using surface plasmon resonance optical sensor - Wan Yusoff, Wan Yusmawati (2005)
Surface plasmon resonance (SPR) spectroscopy is a surface-sensitive technique that has been used to characterize the thickness and index of refraction of dielectric medium at noble metal interface. Nowadays surface plasmon resonance technique has emerged as a powerful technique for a variety of chemical and biological sensor applications. In this study, gold and silver with purity of 99.99% were used to fabricate thin metal films. The thin film was deposited onto a glass cover slip and attached onto the surface of a 60° prism using index matching oil. Liquid samples, such as chlorine, saccharide, swimming pool water, pesticide, virus and DNA were studied using Kretschmann Surface Plasmon Resonance technique. All the measurements were carried out at room temperature. The experiment was carried out by measuring the intensity of the optical reflectivity as a function of incident angle. It found that the shift of resonance angle (.dB) increased linearly with the sample concentration. The detection limit of the sensor was estimated better than 0.01 pM for the sample of DNA (Olig02-Bio). Larger sensor sensitivity of 9.42°/(mol/L) is obtained for the sucrose sample. The kinetic behaviour of the system was also examined to monitor the selfassembling p rocess on the metal surface in real time. The shift in resonance angle increased greatly with time during the increment of the molecules deposited on the gold surface. In contrast it was found decrease with time during self-assembling process. This work also studied the molecule-dielectric interaction for a thin Fatty Hydroxamic Acid (FHA) film (extract from crude palm oil), which the FHA layer was coated using spin coating on the top of metal film. When the medium outside the surface of Au film was changed from air to FHA layer, the resonance angle shifted to the higher value. The shift of resonance angle increased linearly with the increasing concentration FHA layer. When the metal ion was attached to the FHA film, the resonance angle was changed to the maximum value. The experimental results reveal that the technique that based on surface plasmon resonance phenomenon can be used to determine the optical properties and the kinetic behaviour. It also suitable to study the molecule-dielectric interaction for the polymer film. This technique can become an effective chemical optical sensor. Saccharide, pesticide and chlorine concentration in water can be detected using this sensor. Furthermore it also can be used to detect DNA and viruses solution.